Analisis dan Strategi Mitigasi Risiko Produksi Teh Botol Sosro di PT. Sinar Sosro Pabrik Bali - Sari, Ni Made Dwi Astiti; Satriawan, I Ketut; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
This study aims to identify risks, analyze the level of risk priority, and formulate alternative strategies and determine priority risk factors to minimize the risk of Sosro Teh Botol production. This study uses two methods, the Failure Mode and Effect Analysis ( FMEA) method used to assess and determine risk priorities, and the Analytical Hierarchy Process ( AHP) method is used to determine priority risk factors. At PT Sinar Sosro Bali Factory there are 18 risks of Teh Botol Sosro production, which are divided into 5 risk factors, namely: raw materials, water treatment, kitchen, bottling, and finished products. Risk assessment and determination of risk priorities results in a number of risks that have the highest Risk Priority Number (RPN) for each risk factor, namely delays in raw materials for tea and sugar (14.1), damage to water pumping machines (15.8), sugar weighing errors by employees (19.5), broken bottles in the washing machine (18.7), and collisions between products during distribution (17.1). The mitigation strategy is chosen for the raw material risk factor to improve the raw material ordering schedule, the water treatment risk factor to carry out periodic maintenance of the pump engine, the kitchen risk factor to increase the control of the weighing operator, the risk factor for bottling to improve the setting of the bottle washer machine, and the risk factor for the finished product to increase control over the application of the distribution SOP. Keywords: Risk, risk mitigation, FMEA, Teh Botol Sosro